EXAMINING OF SCHOOL CULTURE AT MIDDLE SCHOOLS - Haşim IŞIK (İstanbul Aydın Üniversitesi Dergisi, 2017)
The purpose of this research is to determine the relationship between the demographic structure of the branch teachers and their schools and the aspects of these school cultures. The research was carried out with 237 branch teachers in the middle schools located on the district of Fatih, Istanbul. In this research the data has been collected and evaluated by means of ‘’ the scale of the school culture’’ developed by Ali Rıza TERZİ. According to the teachers genders it ranges as 148 of female, 89 of male. T- Test has been used for comparing the continuous data between the two independent sample groups. As for the other independent groups which are more than two, the one way ANOVA test has been used. In addition to these Scheffe test has been used as a supplement Post-hoc analysis. According to the results of this research the aspect of ‘’Duty Culture’’s frequency rate was higher comparing to other cultures.It hasn’t been found any important difference between school culture dimensions ant gender factor in the research conducted.It has been found impotant differences between school culture dimensions with age and working factor in the same school.